2018
DOI: 10.1159/000485097
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan, a Novel Potassium-Competitive Acid Blocker, Should Be Used for the Helicobacter pylori Eradication Therapy as First Choice: A Large Sample Study of Vonoprazan in Real World Compared with Our Randomized Control Trial Using Second-Generation Proton Pump Inhibitors for Helicobacter pylori Eradication Therapy

Abstract: Background/Aims: Phase III study demonstrated that vonoprazan-based Helicobacter pylori eradication therapy achieved higher eradication rate compared with lansoprazole. However, there is no study that evaluated the efficacy of vonoprazan in a large sample in real world. We investigated the eradication rate and safety of vonoprazan-based eradication therapy compared with our randomized control trial using second-generation proton pump inhibitor (PPIs). Methods: (First study) A total of 147 patients who have H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
(26 reference statements)
2
25
0
Order By: Relevance
“…These results were similar to the Japanese phase III study in which eradication rates of the first-and second-line eradication therapies were 92.6% (300/324) and 98.0% (49/50), respectively [10]. Our results were also similar to the results of post-marketing research that investigated first-line eradication therapy with vonoprazan/AMPC/CAM and reported eradication rates of around 90% [14][15][16][17].…”
Section: Discussionsupporting
confidence: 89%
“…These results were similar to the Japanese phase III study in which eradication rates of the first-and second-line eradication therapies were 92.6% (300/324) and 98.0% (49/50), respectively [10]. Our results were also similar to the results of post-marketing research that investigated first-line eradication therapy with vonoprazan/AMPC/CAM and reported eradication rates of around 90% [14][15][16][17].…”
Section: Discussionsupporting
confidence: 89%
“…There are a few studies concerning the adverse events of second-line eradication therapy with vonoprazan (21,24,29,31,36). These studies showed that adverse events occurred in 0-30% of patients receiving VAM-containing regimens, with diarrhea being the main adverse effect.…”
Section: ) Efficacy Of Vonoprazan For Second-line Eradicationmentioning
confidence: 99%
“…Second, we must consider the various patterns of antibiotic resistance of H. pylori among regions. The Japanese studies described above investigated roughly the same eradication regimens: vonoprazan 20 mg + amoxicillin 750 mg + clarithromycin 200/400 mg or metronidazole 250 mg, twice (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). In Japan, the rate of clarithromycin resistance of H. pylori is more than 30%, whereas that of metronidazole resistance is less than 5% (55).…”
Section: Can Vonoprazan-based Triple Therapy Be Applied To Other Popumentioning
confidence: 99%
“…P-CAB inhibits H + , K + -ATPase-mediated gastric acid secretion, and vonoprazan suppresses gastric acid secretion more potently than PPIs [22][23][24]. There have been many studies indicating that H. pylori eradication with triple therapy including vonoprazan is more efficient compared with eradication using PPIs [25][26][27][28][29][30][31][32][33][34][35][36]. However, these studies did not clearly demonstrate that lifestyle-related factors, including smoking and drinking, had any influence on eradication rates following triple therapy incorporating vonoprazan.…”
Section: Introductionmentioning
confidence: 99%